Quantifying the Impacts of Technology Evolution on B2B Buyer’s Contract Length Decision in Technology Service Market - Qu, Yingge (Journal of Marketing Development and Competitiveness, 2019)
Both the buyer’s contractual decision and the service-related technology evolution play important roles in the Business-to-Business technology service market. However, no empirical research has been done to quantify the relationship between the technology evolution and the buyer’s choices of service contract length. We leverage both the service manager’s practical consideration and the B2B buyer’s service transaction data to understand the effects of technology evolution on the buyer’s contractual length decision. We empirically prove that the technology evolution exhibits multi-dimensional effects on the buyer’s contractual decision. The service providers should strategically manage the technology evolution to optimize the buyer’s service contract length.